Aligning Curriculum, Language, and Learners: An Evaluation of Arabic Reading Materials in Primary Education - Al Maidah, Sandia; Indrianto, Nino; Nasar Bin Madi, Faisol (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study examines the alignment of Arabic reading (maharah qirā’ah) instructional materials with the Indonesian curriculum policy KMA 183 of 2019 and evaluates their linguistic quality and pedagogical relevance in primary education. Using a qualitative content-based approach, the study analyzed an Arabic textbook for Grade 3 through document analysis, classroom observation, and semi-structured interviews. The findings show that the materials are generally aligned with curriculum requirements at the level of early reading competence, particularly in vocabulary recognition and simple sentence structures. However, the linguistic content demonstrates limited variation and a relatively flat progression of difficulty, while reading activities predominantly emphasize decoding and literal comprehension. Observational and interview data confirm that classroom practices largely replicate these patterns, with limited opportunities for contextual meaning-making. The study highlights a gap between curriculum expectations and pedagogical realization, emphasizing the need for instructional materials that better support gradual and meaningful reading development in primary Arabic education.